BOOK REVIEW: WAR CHILDHOOD: SARAJEVO 1992-1995 - PILARSKA, JUSTYNA (Society Register, 2018)
As early as at the beginning of the last century, the Polish-Jewish educator, children›s author, and pedagogue Janusz Korczak called for the right of child to happy childhood. This revelatory vision was accompanied by Hellen Key, who proclaimed 20th century as the century of the child, publishing book of such title and calling for the rights of children to free growth. Unfortunately, the history of the modern world added to these humane ideas rather pessimistic post scriptum, involving children in the armed conflicts and totalitarian regimes, making them the victims of adult cruelty to an unimaginable extend. In such context, the “War Childhood” book provides a very important and exceptional pedagogical and sociological study, for it induces readers to ponder over the position and status of children in armed conflicts, with the biographical, psychological and social repercussion of the latter.